Base-Catalyzed Deprotection of Aldehydes: A New Haloform Reaction - Abulipizi, Gulizhabaier; Abuduwaili, Kadierya; Tian, Shiying; Maihemuti, Mailikezhati; Abulikemu, Abudu Rexit (Synthesis, 2023)
An efficient procedure for the deprotection of α,α,α-trihalogen (Cl, Br) methyl alcohols under mild reaction conditions to produce the corresponding aldehydes and haloforms is described. This method can be applied to the deprotection of aromatic, aliphatic, and heterocyclic trihalomethyl alcohol compounds.
Keywords: trihalohydrins; aldehydes; deprotection; haloform